ИСЛОМ ҚАДРИЯТЛАРИНИ ОИЛАДА ШАКЛЛАНТИРИШ ЖАРАЁНИГА ОТА-ОНАЛАРНИ МАҚСАДЛИ ТАЙЁРЛАШ - Шамуратова, Э.С. (SCIENCE and SOCIETY, 2019)
The article focuses on the purposeful preparation of parents for the process of forming Islamic values in the family. The process of upbringing helps to analyze the issues of assisting parents in providing a healthy spiritual environment in the family.